Geogebra sebagai solusi interaktif untuk pembelajaran matematika yang lebih menarik dan efektif. - rustama, yuniar dwi (Maliki Interdisciplinary Journal, 2025)
The discussion in this article is about the use of GeoGebra as an interactive solution in mathematics learning that aims to increase the attractiveness and effectiveness of the teaching and learning process. GeoGebra is one of the graph-based software that connects algebra, geometry, and calculus, providing a more visual and dynamic approach to understanding mathematical concepts. In addition to being used to visualize abstract theories in students, GeoGebra is also used as an object of interaction on the material being studied. This article examines and synthesizes various studies related to GeoGebra in learning. By collecting and analyzing more than 10 articles published in national journals and international journals. From this analysis, it is concluded that GeoGebra is an interactive solution in creating interesting and effective learning